Experimental research on remote non-contact laser vibration measurement for tunnel lining cavities - Hongyun Yang; Yu Xie; Zhi Lin; Lin Li; Xiang Chen; Wanlin Feng; Honglin Ran; Li He (Scientific Reports)
Abstract The lining cavities in tunnels have strong concealment and pose significant risks, seriously affecting tunnel operational safety. Therefore, it is necessary to develop efficient and high-precision detection techniques for tunnel lining cavities. In this study, concrete slabs with different parameter cavities were selected as the research object, and experiments on remote detection using Laser Doppler Vibrometry were conducted. During the experiments, the vibration parameters of the concrete surface were measured for cavities of varying sizes and depths, filled with different materials, and under different detection distance conditions. The vibration differences between the defective and healthy parts were analyzed using the spatial spectral entropy algorithm. The results showed that for cavities with side lengths of 200mm, depths of 50mm, and filled with hollow wooden boxes, the maximum velocity amplitudes of the surface concrete were 10.68, 3.55, and 4.01 times higher than those of the healthy parts, respectively. Moreover, at the same frequency, larger cavity areas and shallower depths resulted in greater surface vibration amplitudes. The vibration amplitudes of the surface with hollow wooden box filling were higher than those with foam polystyrene board filling. With increasing detection distance, the overall surface vibration velocity of the cavities was higher at a distance of 3 m from the laser probe compared to 5 m, indicating the ability to quantitatively describe the apparent vibration characteristics of concrete cavities under different parameters. This study demonstrates the significant effectiveness of laser Doppler vibrometry in remote detection of lining cavities in tunnels.